Managerial Compensation Duration and Stock Price Manipulation - Josef Schroth (Bank of Canada, 2015)
I build a model of optimal managerial compensation where managers each have a privately observed propensity to manipulate short-term stock prices. It is shown that this informational asymmetry reverses some of the conventional wisdom about the relationship between reliance on short-term pay and propensity to manipulate. The optimal compensation scheme features a negative relationship between pay duration and manager manipulation activity, reconciling theory with recent empirical findings (Gopalan et al., 2014). Further, the model predicts that managers who spend more resources manipulating short-term stock prices also put more effort into generating longterm firm value.
Keywords: D82; G14; G30; M12; 330; Labour markets; Economic models; Recent economic and financial developments